E-tourism Kota Tobelo Kabupaten Halmahera Utara - Stefan F. Pangalila; Arie S.M. Lumenta; Nancy J. Tuturoong (Universitas Sam Ratulangi, 2014)
Abstract - One very big in the presentation of information today is the need for the media information that is often used by the general public, companies, and state agencies. Crate Tobelo town which is a tourist spot that is not yet fully known to outsiders about the beauty of the tourist spot. Web programming has grown rapidly with many advantages that can be accessed diberbagi no such place. E-tourism Tobelo City North Halmahera using extreme programming as a methodology that includes plenning, design, coding, release. The results of this study lead to the conclusion. With the E-tourism Tobelo City North Halmahera then the tourists can be easier to search for information about KotaTobelo. The tourists get to know the culture in City Tobelo. The tourists are easier to get to know and know the language Tobelo City. Keywords :E-tourism, extreme programming, information, travel. Abstrak - Salah satu yang sangat besar dalam penyajian informasi sekarang ini adalah kebutuhan akan media informasi yang sering dipakai oleh masyarakat umum, perusahaan, dan instansi-instansi negara. Sepeti Kota Tobelo yang merupakan tempat wisata yang belum sepenuhnya dikenal pihak luar mengenai keindahan tempat wisatanya. Pemrograman web telah berkembang dengan pesat dengan banyak kelebihan yang ada seperti bisa diakses diberbagi tempat. E-tourism Kota Tobelo Kabupaten Halmahera Utara menggunakan extreme programming sebagai metodologi yang mencakup plenning, design, coding, rilis. Hasil dari penelitian ini memberikan kesimpulan. Dengan adanya E-tourism Kota Tobelo Kabupaten Halmahera Utara maka para wisatawanÂ dapat lebih mudah untuk mencari informasi tentang KotaTobelo. Para wisatawan lebih mengenal kebudayaan yang ada di Kota Tobelo. Para wisatawan lebih mudah untuk lebih mengenal dan mengetahui bahasa Kota Tobelo. Kata kunci :E-tourism, extreme programming,informasi, wisata.